PENGARUH PERSEPSI KEMANFAATAN, PERSEPSI KEMUDAHAN PENGGUNAAN DAN DAYA TARIK PROMOSI TERHADAP MINAT BELI DI GRAMEDIA ONLINE - Adrian,; Riki, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2022)
The research aims to find out the influence of use fullness perception, ease of use and promotion attraction on the willingness to buy on Gramedia Online. The study used census methods, namely dataring the entire existing population. Based on the census in the field, then samples in the study were as many as 45 customer. Data is collected by questionnaire technique. In the results of this study there was a negative effect between use fullness on willingness to buy with counting grades Y = 1,042+ 0,10X1 + 0,400X2 + 0,389X3+e. variables use fullness perception there was a negative influence between use fullness perception on willingness to buy with counting grades thitung (0,136) < ttabel (2.01954), Variable ease of use there was an influence between ease of use on willngnes to buy with counting values thitung (5,905) > ttabel (2.01954), promotion attraction variables exist the influence between promotion attracton on willingness to buy with counting value thitung (4,089) > ttabel (2.01954). as well as use fullness perception, ease of use and promotion attraction have simultaneous effect on willingness to buy by calculation suggesting that Fhitung adalah 73,125 with a Fhitung value signification of 0,001 lower than 0.05. Whereas the R Square value of 0,843 or 84.3%, means that independent variables are able to explain the dependent variables of 84.3%, while the rest of the amount of 15.7% is offered by other variables that do not enter the study.